Mobile ticketing readiness for public railway transportation organization / Masita Miskam - Miskam, Masita (2006)
Mobile ticketing technology has been successfully implemented in some foreign countries. However, Malaysia still not shows any indication to apply the technology. Nonetheless, the researcher cannot simply make an assumption about the level of readiness in the public transportation organization. This study is undertaken (1) to identify current ticketing system being practice in public railway transportation, (2) to determine the level of readiness towards mobile ticketing for public railway transportation and (3) to identify the factors that influence to the level of readiness towards mobile ticketing.